Sustained Within-season Vaccine Effectiveness Against Influenza-associated Hospitalization in Children: Evidence From the New Vaccine Surveillance Network, 2015–2016 Through 2019–2020. (22nd July 2022) - Sahni, Leila C; Naioti, Eric A; Olson, Samantha M; Campbell, Angela P; Michaels, Marian G; Williams, John V; Staat, Mary Allen; Schlaudecker, Elizabeth P; McNeal, Monica M; Halasa, Natasha B; Stewart, Laura S; Chappell, James D; et al.
Abstract: Background: Adult studies have demonstrated within-season declines in influenza vaccine effectiveness (VE); data in children are limited. Methods: We conducted a prospective, test-negative study of children 6 months through 17 years hospitalized with acute respiratory illness at 7 pediatric medical centers during the 2015–2016 through 2019–2020 influenza seasons. Case-patients were children with an influenza-positive molecular test matched by illness onset to influenza-negative control-patients. We estimated VE [100% × (1 – odds ratio)] by comparing the odds of receipt of ≥1 dose of influenza vaccine ≥14 days before illness onset among influenza-positive children to influenza-negative children. Changes in VE over time between vaccination date and illness onset date were estimated using multivariable logistic regression. Results: Of 8430 children, 4653 (55%) received ≥1 dose of influenza vaccine. On average, 48% were vaccinated through October and 85% through December each season. Influenza vaccine receipt was lower in case-patients than control-patients (39% vs 57%, P < .001); overall VE against hospitalization was 53% (95% confidence interval [CI]: 46, 60%). Pooling data across 5 seasons, the odds of influenza-associated hospitalization increased 4.2% (−3.2%, 12.2%) per month since vaccination, with an average VE decrease of 1.9% per month (n = 4000, P = .275). Odds of hospitalization increased 2.9% (95% CI: −5.4%, 11.8%) and 9.6% (95% CI: −7.0%, 29.1%) per month in children ≤8 years (n = 3084) and 9–17 years (n = 916), respectively. These findings were not statistically significant. Conclusions: We observed minimal, not statistically significant within-season declines in VE. Vaccination following current Advisory Committee on Immunization Practices (ACIP) guidelines for timing of vaccine receipt remains the best strategy for preventing influenza-associated hospitalizations in children. Abstract : In this test-negative design study, the overall odds of influenza-associated hospitalization increased 4.2% (−3.2%, 12.2%) per month with a corresponding average decrease in vaccine effectiveness (VE) of 1.9% per month ( P = .275). This was not statistically significant.